Spatio-temporal Mapping Of Dengue Disease In Peninsular Malaysia - Abd Naeeim, Nurul Syafiah (2021)
The urgent need for more effective public health measures to control dengue disease as well as other infectious diseases in Malaysia drove the decision to undertake the work in this thesis. The main objective of this thesis is to expand several prominent issues in disease mapping related to dengue disease. Spatial and temporal pattern of the dengue disease using appropriate statistical modeling were carried out and visualised through mapping techniques. To achieve the main objective, first, the risk of dengue disease were estimated spatially, temporally and spatio-temporally by taking into account the information from nearby areas, previous time points and also the interaction between areas and time points using several different methods. Then, this study identified the existence of any spatial and temporal cluster of high dengue risk. Lastly, this study examined the relationship between dengue risk with several climate variables namely temperature, total number of rainfall and relative humidity. The main methodology of this study involved Bayesian estimation with Integrated Nested Laplace Approximation (INLA) approximation. The models for dengue risk calculation were formed based on Bayesian Hierarchical Model (BHM) for discrete spatio-temporal model and Stochastic Partial Differential Equation (SPDE) for continuous spatio-temporal model and their comparison had been carried out